One drug for two targets: Biological evaluation of antiretroviral agents endowed with antiproliferative activity. Issue 11 (1st June 2017) - Botta, Lorenzo; Maccari, Giorgio; Calandro, Pierpaolo; Tiberi, Marika; Brai, Annalaura; Zamperini, Claudio; Canducci, Filippo; Chiariello, Mario; Martí-Centelles, Rosa; Falomir, Eva; Carda, Miguel
Graphical abstract: Abstract: AIDS-related cancer diseases are malignancies with low incidence on healthy people that affect mostly subjects already immunocompromised. The connection between HIV/AIDS and these cancers has not been established yet, but a weakened immune system is certainly the main cause. We envisaged the possibility to screen a small library of compounds synthesized in our laboratory against opportunistic tumors mainly due to HIV infection like Burkitt's Lymphoma. From cellular assays and gene expression analysis we identified two promising compounds. These derivatives have the dual action required inhibiting HIV replication in human TZM-bl cells infected with HIV-1 NL4.3 and showing cytotoxic activity on human colon HT-29 and breast adenocarcinoma MCF-7 cells. In addition, preclinical in vitro adsorption, distribution, metabolism, and excretion studies highlighted a satisfactory pharmacokinetic profile.